CHEMICAL QUALITY OF RICE STRAW SILAGE SUPPLEMENTED WITH GLIRICIDIA AND CALLIANDRA LEAVES - I W. M., Arta; Cakra, I G. L. O.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2020)
The study aimed to determine the chemical quality of rice straw silage supplemented with gliricidia and calliandra leaves.  The study used a completely randomized design (CRD), consisting of four (4) treatments and each treatment was repeated five (5) times.  The treatments given were: P0 (90% rice straw + 5% molasses + 5% polar), P1 (60% rice straw + 30% gamal leaves + 5% molasses + 5% polar), P2 (60% rice straw + 15 % gamal leaves + 15% calliandra leaves + 5% molasses + 5% polar) and P3 (60% rice straw + 30% calliandra leaves + 5% molasses + 5% polar).  The variables observed in the study were chemical quality, namely: dry matter content, water content, organic matter, ash content, crude protein, crude fiber, gross energy, crude fat, TDN and BETN. Chemical quality of P1 treatment is 94,667% dry matter, 5,333% water content, 84,934% organic matter, 15,066 ash content, 17,759% crude protein, 23,355% crude fiber, 3,800 Kcal/g gross energy, 5,726% crude fat, 31,832% TDN and 32,761% BETN. The chemical quality of P2 treatment is 95.692% dry matter, 4.308% water content, 87.625% organic matter, 12.3755 ash content, 14.277% crude protein, 21.196% crude fiber, 4.041 Kcal/g gross energy, 4.989% crude fat, 35.757% TDN and 42.854% BETN. The chemical quality of P3 treatment is 96,644% dry matter, 3,356% water content, 87,353% organic matter, 12,647% ash content, 15,102 crude proyein, 22,029 crude fiber, 4,011 Kcal/g gross energy, 3,735 crude fat, 32,519a TDN and 43,131 BETN. Based on the research results, it can be concluded that gliricidia and calliandra leaf supplementation can improve the chemical quality of rice straw silage. Keywords: rice straw, chemical quality silage, supplementation, gliricidia leaves, calliandra leaves